Features of immunohistochemical diagnostic of melanocytic tumours. - Shpon’ka, I. S.; Poslavs’ka, O. V.; Gritsenko, P. O.; Lymar, L. I.; Shpon’ka, V. I. (Морфологія / Morphologia / Morfologìâ, 2013)
Background. The malignant melanomas are the most important group of skin cancers. Although less common than the familiar basal and squamous cell tumours of the skin, they are much more frequently fatal, due to their intrinsic tendency to lymphatic and haematogenic metastasis. Objective. The article is devoted to parsing cases melanocytic tumours that were established through immunohistochemical study. Methods. In the study analyzed 236 patient material (150 women and 86 men) aged 28 to 77 years during 2010-2013 turned out to clarify the histological diagnosis of skin tumors or metastases to lymph nodes (rare at other sites). The primary monoclonal antibodies used Сytokeratin, Рan Ab1 (clone AE1/AE3), S100 (clone 4C4.9), Ki-67 (clone SP6), Vimentin (clone V9), Melanoma gp100 (clone HMB-45). Results. Naevus proliferation rate showed a statistically significant difference with respect to proliferation rate of malignant melanomas (p<0,05). All samples (100%) showed positive expression of high-intensity staining (+++) or moderate (++) intensity on the marker S100; 98,30% of samples (232 of 236) showed positive expression of marker HMB-45 at least in terms of tumor cells with intensity color from the high (+++) to weak (+) and 83.89% of the samples (198 of 236) were negative (–) Сytokeratin, Рan Ab1 (other 38 cases showed weakly positive expression (+/–) of tumor cells). Conclusions. 1. In the differential diagnosis of melanoma and naevus, we must bear in mind the uniformity immunophenotype of these tumors and consider only the cytological features of the tumor, changes in the structure of the epidermis and dermis (contour, symmetry, depth, inflammatory infiltration) and proliferation rate. 2. Patients whose lymph nodes were the first clinical signs of cancer are always in need for additional immunohistochemical studies to avoid diagnostic errors. 3. The most common phenotype of melanocytic tumours responsible Сytokeratin, Рan–, Vimintin+, S100+, HMB-45+, which involves the use of these markers together. 4. Some options melanomas (especially amelanotic) can significantly alter their immunophenotypes, making it difficult to verify these tumors and needs to be extended diagnostic panel of antibodies.